Owner Personality, Owner-Dog Attachment, and Canine Demographics Influence Treatment Outcomes in Canine Behavioral Medicine Cases - Powell, Lauren; Stefanovski, Darko; Siracusa, Carlo; Serpell, James (Frontiers in Veterinary Science, 2021)
Human and canine parameters can affect the development of canine behavior problems, although their influence on the dog's response to veterinary behavioral treatment remains unclear. This study aimed to investigate the possible associations between canine behavior following clinical intervention and canine demographic characteristics, owner personality and owner-dog attachment. The study included 131 dog-owner dyads who attended a veterinary behavioral service. Owners completed the C-BARQ at baseline, 3-months and 6-months, and the 10 Item Personality Inventory and Lexington Attachment to Pet Scale at baseline. Data were analyzed for the effect of clinical intervention on C-BARQ subscale scores using mixed effect models. Binary logistic regression models were used to analyze the association between behavior change and canine and owner parameters. Within 6-months of veterinary consultation, trainability increased (coefficient 0.03, p = 0.01) and chasing (coefficient −0.04, p = 0.02), separation-related behavior (coefficient −0.04, p = 0.01) and energy level (coefficient −0.04, p = 0.05) decreased. Treatment outcomes were associated with both canine and owner variables. Canine behavior at baseline was the most consistent predictor of behavior change with less desirable baseline behavior associated with greater odds of decreased problem behavior at three- and 6-months post-consultation across most C-BARQ subscales. Canine age and weight; owner conscientiousness, extraversion and openness; and owner-dog attachment were also associated with treatment outcomes for some behavioral categories. These findings could be used by veterinarians to formulate more accurate prognoses and provide owners with targeted advice to reduce the influence of background factors on the dog's response to clinical behavioral intervention.